2023
DOI: 10.3389/fbioe.2023.1286955
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study: green synthesis and evaluation of MgO/C-dots/DOX phosphorescent nanocomposites for photodynamic/photocatalytic therapy of tumors

M. Karimi,
E. Sadeghi,
M. Zahedifar
et al.

Abstract: MgO nanoparticles (NPs) and carbon dots (C-dots) were synthesized by co-precipitation and hydrothermal techniques. In the next step, as-synthesized NPs were modified by C-dots. Then, polyethylene glycol (PEG) was conjugated with MgO/Cdots. Finally, Doxorubicin (Dox) as an anticancer drug was loaded on MgO/Cdots/PEG nanocomposites. The XRD pattern showed the characteristic peaks of C-dots and MgO. The FTIR spectrum showed that MgO/C-dots possessed the carboxyl functional groups, allowing DOX to be loaded onto M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Consequently, the surface of the bacterial strains leads to either inhibition of bacterial growth or killing of both bacterial cells. [12,13] Thus, it can be observed that SC1 has a higher level of bacterial deactivation than SC, SC2, and SC3. Furthermore, the surface morphology reveals that the Smdoped CuO nano-lanceolates annealed at the comparatively low temperature of 300 °C have outstanding antibacterial activity, with the lanceolate-like structure and widening band gap being important contributors.…”
Section: Pl Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the surface of the bacterial strains leads to either inhibition of bacterial growth or killing of both bacterial cells. [12,13] Thus, it can be observed that SC1 has a higher level of bacterial deactivation than SC, SC2, and SC3. Furthermore, the surface morphology reveals that the Smdoped CuO nano-lanceolates annealed at the comparatively low temperature of 300 °C have outstanding antibacterial activity, with the lanceolate-like structure and widening band gap being important contributors.…”
Section: Pl Spectramentioning
confidence: 99%
“…[4] Few research findings also suggest that suitable photons of the proper wavelength are used to illuminate the nanoparticles which contribute to the enhanced antibacterial activity because of the production of reactive oxygen species (ROS), mostly hydroxyl radicals of H 2 O 2 and singlet oxygen. [11][12][13] Moreover, because of their distinctive optical characteristics, rare earth elements are frequently selected as prospective dopants for antibacterial examination. Researchers have recently become intrigued about trivalent rare earth ions (Tb 3 + , Er 3 + , Ce 3 + , Dy 3 + , Tm 3 + , and Sm 3 + ) doped with metal oxides [14][15][16][17] due to their numerous applications which include photocatalysis, [17] optoelectronics, [14] PEC energy devices, [16] and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%